2008
DOI: 10.1038/nature07510
|View full text |Cite
|
Sign up to set email alerts
|

Transcription inactivation through local refolding of the RNA polymerase structure

Abstract: Structural studies of antibiotics not only provide a short cut to medicine allowing for rational structure-based drug design, but may also capture snapshots of dynamic intermediates that become ‘frozen’ after inhibitor binding1,2. Myxopyronin inhibits bacterial RNA polymerase (RNAP) by an unknown mechanism3. Here we report the structure of dMyx—a desmethyl derivative of myxopyronin B4—complexed with a Thermus thermophilus RNAP holoenzyme. The antibiotic binds to a pocket deep inside the RNAP clamp head domain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
182
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(193 citation statements)
references
References 31 publications
10
182
1
Order By: Relevance
“…6 New opportunities to explore bacterial RNAP as a target have arisen following the 2008 discovery of the myxopyronin B 1 (MyxB) binding site (Figure 1). 7,8 MyxB is an antibiotic produced from the myxobacterium Myxococcus fulvus Mxf50, which inhibits bacterial RNAP and the growth of Gram-positive and some Gram-negative bacteria [1: IC 50 , 0.92 μM; minimum inhibitory concentration (MIC), 1 μg/mL Staphylococcus aureus]. 9,10 MyxB binds to the switch region of RNAP, where its mode of action has been proposed to involve either inhibition of the opening and closing of the β 0 subunit 8 or stabilization of the refolding of the β 0 -subunit switch-2 region, leading to an inactive conformation that cannot bind to template DNA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…6 New opportunities to explore bacterial RNAP as a target have arisen following the 2008 discovery of the myxopyronin B 1 (MyxB) binding site (Figure 1). 7,8 MyxB is an antibiotic produced from the myxobacterium Myxococcus fulvus Mxf50, which inhibits bacterial RNAP and the growth of Gram-positive and some Gram-negative bacteria [1: IC 50 , 0.92 μM; minimum inhibitory concentration (MIC), 1 μg/mL Staphylococcus aureus]. 9,10 MyxB binds to the switch region of RNAP, where its mode of action has been proposed to involve either inhibition of the opening and closing of the β 0 subunit 8 or stabilization of the refolding of the β 0 -subunit switch-2 region, leading to an inactive conformation that cannot bind to template DNA.…”
mentioning
confidence: 99%
“…9,10 MyxB binds to the switch region of RNAP, where its mode of action has been proposed to involve either inhibition of the opening and closing of the β 0 subunit 8 or stabilization of the refolding of the β 0 -subunit switch-2 region, leading to an inactive conformation that cannot bind to template DNA. 7 As bacteria have become resistant to the rifamycins, the MyxB binding site presents itself as an excellent opportunity for the design of new RNAP inhibitors as the two antibiotic binding sites are distant from each other. 8 Inspection of the available cocrystal structures 7,8 revealed that the MyxB binding site within RNAP is U-shaped and sandwiched between two hydrophobic pockets ( Figure 1a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding transcriptional regulation requires the characterization of the intermediates and checkpoints in the initiation pathway leading to a transcriptionally active RNAP-promoter complex, generically referred to as RP o . The antibiotics lipiarmycin (Lpm) and myxopyronin (Myx), which target two distinct steps in forming RP o , [1][2][3] open up new perspectives for fundamental studies of transcriptional regulation and for medical research to identify new drug target sites. …”
mentioning
confidence: 99%